Land use change using geospatial techniques in upper Prek Thnot watershed in Cambodia - Khorn, Norin; Ismail, Mohd Hasmadi; Kamarudin, Norizah; Abu Bakar, Siti Nurhidayu (Universiti Putra Malaysia Press, 2020)
Monitoring of land use change is crucial for sustainable resource management and development planning. Up-to-date land use change information is important to understand its pattern and identify the drivers. Remote sensing and geographic information system (GIS) have proven as a useful tool to measure and analyze land use changes. Recent advances in remote sensing technology with digital image processing provide unprecedented possibilities for detecting changes in land use over large areas, with less costs and processing time. Thus, the objective of this study was to assess the land use changes in upper Prek Thnot watershed in Cambodia from 2006 until 2018. Geospatial tools such as remote sensing and GIS were used to process and produce land use maps from Landsat 5 TM, Landsat 7 ETM+ and Landsat 8. The post-classification comparison was conducted for analysing the land use changes. Results show forest area was greatly decreased by 1,162.06 km2 (33.67%) which was converted to rubber plantation (10.55 km2), wood shrub (37.65 km2), agricultural land (1,099.71 km2), built-up area (17.76 km2), barren land (3.65 km2), and water body (14.69 km2). Agricultural land increased by 1,258.99 km2 (36.48%), while wood shrub declined by 161.88 km2 (4.69%). Rubber plantation, built-up area, barren land, and water bodies were increased by 10.55 km2 (0.31%), 33.64 km2 (0.97%), 4.87 km2 (0.14%) and 15.89 km2 (0.46%), respectively. The decrease of forest and wood shrub had resulted due to population growth (1.8% from 2008 to 2019) and land Monitoring of land use change is crucial for sustainable resource management and development planning. Up-to-date land use change information is important to understand its pattern and identify the drivers. Remote sensing and geographic information system (GIS) have proven as a useful tool to measure and analyze land use changes. Recent advances in remote sensing technology with digital image processing provide unprecedented possibilities for detecting changes in land use over large areas, with less costs and processing time. Thus, the objective of this study was to assess the land use changes in upper Prek Thnot watershed in Cambodia from 2006 until 2018. Geospatial tools such as remote sensing and GIS were used to process and produce land use maps from Landsat 5 TM, Landsat 7 ETM+ and Landsat 8. The post-classification comparison was conducted for analysing the land use changes. Results show forest area was greatly decreased by 1,162.06 km2 (33.67%) which was converted to rubber plantation (10.55 km2), wood shrub (37.65 km2), agricultural land (1,099.71 km2), built-up area (17.76 km2), barren land (3.65 km2), and water body (14.69 km2). Agricultural land increased by 1,258.99 km2 (36.48%), while wood shrub declined by 161.88 km2 (4.69%). Rubber plantation, built-up area, barren land, and water bodies were increased by 10.55 km2 (0.31%), 33.64 km2 (0.97%), 4.87 km2 (0.14%) and 15.89 km2 (0.46%), respectively. The decrease of forest and wood shrub had resulted due to population growth (1.8% from 2008 to 2019) and land conversion for agricultural purposes. Hence, this study may provide vital information for wise sustainable watershed’s land management, especially for further study on the effect of land use change on runoff in this area.